INFORMAL EDUCATION AS A PROJECTED IMPROVEMENT OF THE PROFESSIONAL SKILLS OF EMPLOYEES OF ORGANIZATIONS - Walidin, Warul (Jurnal Ilmiah Peuradeun, 2016)
Technologies of vocational training play an important role in the concept of informal education and they can be implemented as in higher education, and organizational learning. In the modern understanding of education the two sides are emphasized - the communion of each person to the society and the development of individual personality features. If formal education is moving towards these goals systematically and purposefully at certain training sessions, the place and time of informal education is in no way limited. Informal education can be characterized not only by independent, human progress in cultural development, but also directed and projected improvement of professional and personal skills of employees of organizations. The purpose of this papers to examine informal education not only as an independent, but also as a guide and the projected improvement of the professional and personal skills of employees of organizations. The leading approaches to the study of this problem are social-pedagogical and managerial approaches to substantiate the essence of the process and the role of leaders of organizations trained in the management of such education.